A false-positive ST segment elevation during exercise stress test. (16th April 2013) - Srinivas, Sunil Kumar; Hirapur, Iranna S; Bhairappa, Shivakumar; Manjunath, Cholenahally Nanjappa
Abstract : A 56-year-old man with multiple risk factors undergoing evaluation for chest pain developed ST elevations in multiple leads during exercise stress test. These ST elevations were not classical of ischaemic pattern. The coronary angiogram showed normal coronaries. The false-positive ST elevation was due to an error in the computer-synthesised averaging algorithm.